Health and Retirement of Older New Zealanders - Emma Gorman; Grant M Scobie; Andy Towers (New Zealand Government, The Treasury, 2012)
Increasing life expectancies and uncertainty about future retirement incomes are likely to lead to various changes in behaviour. As expectations are revised, one potentially important adjustment mechanism is in labour force participation rates. There is already evidence these are rising for those beyond the age of eligibility for New Zealand Superannuation. This paper uses a new source of longitudinal data on the health, labour force participation and retirement decisions of older New Zealanders. The central question addressed is the extent to which labour force participation of older New Zealanders is influenced by their health status (both mental and physical), in addition to a wide range of economic, social and demographic variables. Discrete choice models are employed, and particular attention is given to the potential effects of unobserved heterogeneity. We find a range of factors to be associated with the decision to retire, notably health status, marital status and financial incentives. After accounting for the confounding influence of unobservables, we find that physical health remains a determinant of labour force exit for older males. Further, we estimate both the marginal and aggregate effects of specific chronic conditions on labour force participation.
Keywords: J26; J14; J21; I10; 330; Labour force participation; Health; Retirement; New Zealand; Longitudinal survey; Gesundheit; Soziale Lage; Erwerbstätigkeit; Ältere Arbeitskräfte; Flexible Altersgrenze; Neuseeland